DMF-T index and performed treatment index of patients in Conservative Dentistry Installation - Nurrahim, Muhammad Adri; Sukartini, Endang; Hayati, Ayu Trisna (Padjadjaran Journal of Dentistry, 2014)
Introduction: DMF-T index is an important indicator to assess oral health status of the population. DMF-T index is a number that indicates the average total number of permanent teeth affected by caries, missing or should be extraction because of caries, or have been restorated on each tooth and not each surface. DMF-T index being a reference of the Performed Treatment Index (PTI) which is the sum percentage of restored teeth or without caries in the population. The purpose of this study is to determine DMF-T index and performed treatment index of the patient in Dental Conservation Installation.Methods: This research used the descriptive with survey techniques. Sampling was conducted with a total sampling. The DMF-T index and PTI of Patients in Dental Conservative Installation on July – September 2011. The data obtained through clinical examination of 561 respondents. Results: The DMF-T index patients in Dental Conservative Installation is 5.824 while the PTI is 1.51%. Conclusion: DMF-T index of patients in Dental Conservative Installation period July - September 2011 in the high category and PTI Patients In Dental Conservative Installation Oral and Dental Hospital Faculty of Dentistry Universitas Padjadjaran period July - September 2011 in the low category.